2016
DOI: 10.1007/s10441-016-9290-3
|View full text |Cite
|
Sign up to set email alerts
|

Mathematical Model of the Dynamics of Fish, Waterbirds and Tourists in the Djoudj National Park, Senegal

Abstract: In the present paper, we propose and analyze a harvested predator-prey model that incorporates the dynamics of tourists in the Djoudj National Park of Birds, Senegal. The model describes the impact of migration of waterbirds and seasonal fishing on the global coexistence of species in the site of the Djoudj. By the Mahwin continuation theorem of coincidence degree theory, we investigate the existence of a positive periodic solution. The global asymptotic stability is discussed by constructing a suitable Lyapun… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 10 publications
0
1
0
Order By: Relevance
“…Casagrandi and Rinaldi's model was likely one of the first works that related the notion of sustainability with structural properties of stable equilibria points. From the dynamical systems perspective, other authors have analyzed how the forest resources and the wildlife are affected by the tourists (Afsharnezhad & Monfared, 2017; Behjaty & Monfared, 2019; Casagrandi & Rinaldi, 2004; Diop & Sène, 2016, 2018; Kaslik & Neamtu, 2020; Lacitignola et al, 2007; Monfared et al, 2016). Through these models, it can be concluded that these socioecological systems might present sustainable scenarios of the coexistence of tourists and nature.…”
Section: Introductionmentioning
confidence: 99%
“…Casagrandi and Rinaldi's model was likely one of the first works that related the notion of sustainability with structural properties of stable equilibria points. From the dynamical systems perspective, other authors have analyzed how the forest resources and the wildlife are affected by the tourists (Afsharnezhad & Monfared, 2017; Behjaty & Monfared, 2019; Casagrandi & Rinaldi, 2004; Diop & Sène, 2016, 2018; Kaslik & Neamtu, 2020; Lacitignola et al, 2007; Monfared et al, 2016). Through these models, it can be concluded that these socioecological systems might present sustainable scenarios of the coexistence of tourists and nature.…”
Section: Introductionmentioning
confidence: 99%